Demonstration of the Medical Knowledge Pediatric Milestone - Sandra Moore; Meisha Graham; Yolanda Wimberly; Yasmin Tyler-Hill; Chevon Brooks; Fengxia Yan; John Frohna (Association of American Medical Colleges, 2015)
Abstract Introduction The Accreditation Council for Graduate Medical Education (ACGME) pediatric section now requires every pediatric residency program to report the developmental progress of each of its residents in each of the 21 pediatric milestones. Pediatric program directors are expected to educate faculty and residents on how to assess the pediatric milestones. To date, most of the education has consisted of theoretical framework and potential tools to evaluate resident performance of milestones. This video was developed primarily as a faculty development tool for the pediatric milestones, using the medical knowledge milestone as an example. Methods The video demonstrates a typical inpatient pediatric medical team rounding. Specifically, it contains a typical inpatient rounding scenario with an attending, two residents, and a medical student. The scenario was the presentation of a toddler with an acute wheezing episode (a common pediatric inpatient diagnosis) and the team members arriving at the most appropriate diagnosis based on medical knowledge and knowledge of resources (pediatric milestone of medical knowledge). During the video learners complete the included Demographics, Character Rating, and Feedback Form, before participating in a debriefing. Results This resource was produced as a scholarly project for the Association of Pediatric Program Directors Leadership in Educational Academic Development (LEAD). The full project was described to the entire LEAD 2014 cohort in March 2014. It has also been shared with at least 12 program directors, with > 90% noting that it has "very helpful" or "helpful" and 100% wanting additional information. Two programs reported using it with their faculty and thought it was very helpful. Discussion This resource has several limitations. Firstly, the participants must have baseline knowledge of the Pediatric Milestone Project and agree that Milestones are a good way to evaluate learners. If this is not the case, the participants' discussion may focus on the validity of Milestones as a means to evaluate resident performance, as opposed to how to effectively evaluate learners using the Milestones. Secondly, participants should understand that while this video demonstrates a common scenario, residents should demonstrate behaviors consistently over time to be evaluated at that level. However, the greatest strength of this educational resource is its universality. It can also be tailored to complement any curricula for both faculty and residents.